Temperature and Stretching Effects on Complementarity Determining Regions (CDRs) Conformation and Stability of Nimotuzumab F(ab)-Fragment - T.S. Humani; M.A. Martoprawiro; A. Mutalib (PPIKSN-BATAN, 2015)
Nimotuzumab is a humanized monoclonal antibody (mAb), a potential anticancer against epidermal growth factor receptor (EGFR)overexpressed by glioma, head and neck, lung, ovarium, and colon cancers. The combination of its use with both external and internal beam radiotherapies showed improvement of the therapeutic effect. However, the high molecular weight slows its uptake on tumor cells. In a recent development, nimotuzumab has been fragmented and then labeled using diagnostic and therapeutic radionuclides, such as gallium-68, yttrium-90, lutetium-177, and holmium-166. In that preparation, nimotuzumab is often conditioned in various environments with variations of pH, temperature and the presence of other compounds. In this research, molecular dynamics (MD) simulation have been carried out to study the CDRs conformational change of nimotuzumab due to the effect of temperature, and also steered molecular dynamics (SMD) simulation to study the stability of nimotuzumab domain as a result of external forces. The simulations were performed using the Not Just Another Molecular Dynamics (NAMD) program package and the analysis was performed with the Visual Molecular Dynamics (VMD) program package. Based on the stability analysis of each residue on the heavy chain, the active site (CDR3 region) that is at residues numbered 98 (Tryptophan) and 99 (Phenylalanine) has the highest conformational changes. On the light chain, the change occurs at residues numbered 1 (Aspartat), 127 (Serin), and 186 (Tyrosine); and that none of that residues is part of active site or CDRs region of the light chain. The SMD simulation was carried out by fixing the N-terminal end of the heavy chain and applying external forces to the C-terminal end. The pulling was set at a constant velocity of 0.5 Å/ps. The force peak arising at the beginning of the unfolding process is 1226 pN. This force was allegedly caused by the rupture of hydrogen bonds between the heavy chain residue VAL211 (Valine) and the heavy chain residue TYR194 (Tyrosine).Received: 04 October 2014; Revised: 13 March 2015; Accepted 23 March 2015